Synthesis, biological activity and molecular modelling studies of shikimic acid derivatives as inhibitors of the shikimate dehydrogenase enzyme of Escherichia coli - Dulce Catalina Díaz-Quiroz; César Salvador Cardona-Félix; José Luis Viveros-Ceballos; Miguel Angel Reyes-González; Franciso Bolívar; Mario Ordoñez; Adelfo Escalante (Taylor & Francis Group, 2018)
Shikimic acid (SA) pathway is the common route used by bacteria, plants, fungi, algae, and certain Apicomplexa parasites for the biosynthesis of aromatic amino acids and other secondary metabolites. As this essential pathway is absent in mammals designing inhibitors against implied enzymes may lead to the development of antimicrobial and herbicidal agents harmless to humans. Shikimate dehydrogenase (SDH) is the fourth enzyme of the SA pathway. In this contribution, a series of SA amide derivatives were synthesised and evaluated for in vitro SDH inhibition and antibacterial activity against Escherichia coli. All tested compounds showed to be mixed type inhibitors; diamide derivatives displayed more inhibitory activity than synthesised monoamides. Among the evaluated compounds, molecules called 4a and 4b were the most active derivatives with IC50 588 and 589 µM, respectively. Molecular modelling studies suggested two different binding modes of monoamide and diamide derivatives to the SDH enzyme of E. coli.